Structural and optical properties of low cost zinc silicate-based glass ceramics doped with europium - Sheh Omar, Nur Alia (2016)
To date, the demand for better light emitting diodes (LEDs) has led to growing interest in producing Zn2SiO4 based glass ceramic phosphors using waste materials. In this research, low cost Zn2SiO4:xEu3+ phosphors were prepared based on a solid state method using recyclable glass wastes as silica source. The influence of Eu3+ ions (x = 0, 1, 2, 3, 4 and 5 wt.%) and the effect of sintering temperatures, ranging from 600 to 1000 °C on the structural, morphological and optical properties of the phosphors were also investigated using X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, Ultraviolet-visible near infrared (UV-Vis-NIR) spectroscopy and Photoluminescence (PL) spectroscopy. These glass ceramics showed the increasing densities with increasing Eu3+ and sintering temperature. Structural investigation using XRD had revealed that the higher intensities of the diffraction peaks were due to sintering temperatures. Furthermore, their diffraction peaks had slightly shifted to lower diffraction angles when the dopant’s concentration was increased. The morphologies from FESEM analysis showed the formation of densely packed grains and smooth surfaces with the increment of sintering temperatures and addition of dopants. FTIR spectra showed that the progression of sintering temperature has narrowed the broad bands of SiO4 and ZnO4 at 1000 °C. All the broad bands were reduced to smaller bands after the addition of dopant. Additionally, the effects of sintering temperatures and dopants on the samples were apparent on the Raman spectra, which showed the narrow width of Raman lines and the shifted energy region in the spectrum. Most importantly, the largest optical band gaps of the samples were found at the highest sintering temperature. Meanwhile, Eu3+ doped samples have shown the largest optical band gap at 1000 °C upon the examination of the Moss- Burstein effect. Results for the photoluminescence showed red luminescence emissions at 600 nm due to Eu3+ transitions under 400 nm excitation. It was observed that sintering temperatures of 900 and 1000 °C have decreased the intensity of emission, while the highest doping concentration of 5 wt.% of Eu3+ has shown the highest emission intensity of the phosphors. Apart from that, waste silica sources have proven to have excellent crystallinity, surface morphology, optical band gap and emission intensity for obtaining red emitting phosphors, which could also be useful for white LEDs.